OS PRINCÍPIOS ORGANIZADORES DE UM GRUPO OPERATIVO: COMO O VÍNCULO OPERA NA FORMAÇÃO ACADÊMICA - Campos, Iris F. A.; Sonego, Joseila; Rios, Karina R.; Dreher, Daniela Z.; Trevisan, Gisele; Boff, Viviane S. (Salão do Conhecimento, 2013)
Resumo